2015
DOI: 10.1088/0143-0807/36/4/045014
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the impact of question structure on the performance of first year physics undergraduate students at the University of Cambridge

Abstract: We describe a study of the impact of exam question structure on the performance of first year Natural Sciences physics undergraduates from the University of Cambridge. The results show conclusively that a student's performance improves when questions are scaffolded compared with university style questions. In a group of 77 female students we observe that the average exam mark increases by 13.4% for scaffolded questions, which corresponds to a 4.9 standard deviation effect. The equivalent observation for 236 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 14 publications
1
13
0
4
Order By: Relevance
“…Of all exam questions, L exhibits one of the most significant differences in performance between genders, and H shows no significant difference. The scaffolding gains are comparable to those observed in [15] (13.4% for females, 8.8% for males). We conclude that scaffolding may play a role in reducing the gender gap in specific types of problems which were previously identified to contain a male bias, namely questions involving multi-dimensional context.…”
Section: Questions Of Interestsupporting
confidence: 76%
See 2 more Smart Citations
“…Of all exam questions, L exhibits one of the most significant differences in performance between genders, and H shows no significant difference. The scaffolding gains are comparable to those observed in [15] (13.4% for females, 8.8% for males). We conclude that scaffolding may play a role in reducing the gender gap in specific types of problems which were previously identified to contain a male bias, namely questions involving multi-dimensional context.…”
Section: Questions Of Interestsupporting
confidence: 76%
“…Although not as clear, the data does at first glance seem to support the conclusions of [15]. Male students outperform female students on the low scaffolding questions by 2.9% (p = .087), and by only 1.4% on the high scaffolding questions (p = .42).…”
Section: B Gains By Gendermentioning
confidence: 70%
See 1 more Smart Citation
“…In many cases the scaffolding the researchers utilized included examples such as prompting students to complete more specific sub questions instead of one larger question. 154 The results from this study showed that scaffolding questions can benefit all undergraduate students but seemed to particularly have a positive influence on female students' exam performance. Students' expectations going into taking an exam can influence how students respond to the questions.…”
Section: Review Of How Exam Questions Are Written/constructedmentioning
confidence: 76%
“…material is actually included on the exam, students may get an incorrect answer on the exam, not from lack of understanding about the content but because of their preconceived conceptions of the questions. 154 When a complex diagram or information was presented to students in another study conducted by Crip and Sweiry 156 , the students (sometimes incorrectly)…”
Section: When a Mismatch Exists Between What Materials Students Expectmentioning
confidence: 99%